Gender Gap in Workforce Participation in West Nusa Tenggara Province - Gusti Ayu Arini; Ida Ayu Putri S; Tuti Handayani; Saripta Wijimulawiani; Taufiq Chaidir (Eduvest - Journal of Universal Studies, 2026)
Gender participation gap in the workforce is influenced by various factors, including income, age, education, marital status, family size, culture, and social norms. In Nusa Tenggara Barat (NTB), understanding these factors is crucial to addressing gender disparities in employment participation. Despite widespread acknowledgment of cultural and social norms affecting gender roles, their actual impact on workforce participation remains unclear. This study aims to analyze the impact of income, age, education, marital status, family size, culture, and social norms on the gender participation gap in the workforce in NTB. This explanatory research uses a survey sampling method, with 140 respondents. The data is analyzed using multiple linear regression to test and estimate the hypotheses. The hypothesis testing reveals that income significantly affects the gender participation gap in the workforce. However, age, education, marital status, family size, and the cultural and social norm control factors were not found to have a significant impact on the gap in NTB. Culture and social norms, although expected to influence gender roles and household work division, did not significantly contribute to the differences in work hours between men and women. The study concludes that while income plays a significant role in gender workforce participation in NTB, cultural and social norms are not as influential as anticipated. Further research may explore the deeper effects of these norms on gender roles and expectations in the workforce.